Development of a Web-Based Pet Welfare Community - Mahadi, Nurfiryal Awatif; Mohammed Alduais, Nayef Abdulwahab (Applied Information Technology And Computer Science, 2024)
This project revolves around the domain of pet welfare and addresses as critical issue where essential information is often withheld due to the prevalence of traditional methods. This platform aims to provide a centralized space for community engagement, streamline the pet adoption process through digitization, and establish a reliable lost and found system. The project's scope includes connecting individuals with a shared commitment to pet welfare, facilitating easy communication on missing or found pets, and simplifying the search and filtering of pet ads. Implemented in phases using the Waterfall Model technique, the project utilizes Visual Studio Code for web development and phpMyAdmin to administer the system's database. The developed website is an enhanced pet welfare platform that can easily post adoption listings, and report lost and found pets, which not only improves pet welfare but also fosters a supportive community dedicated to the well-being of animals. Some of the future works that can be enhanced for this platform include the integration with social media and enhancement to the existing module where the data can be used to make informed decisions.